Kinetic Studies of the Toxicological Effect of 2-Chlorophenol and 4-Chlorophenol on Alkaline Phosphatase Activity in vitro - Liu, Qiongyu; Zhou, Peijiang; Chen, Yan; Zhan, Hongju; Pan, Keliang (Asian Journal of Chemistry, 2012)
The inhibition kinetic parameters of 2-chlorophenol and 4-chlorophenol on bovine intestinal mucosa alkaline phosphatase activity were studied by spectrophotometry. Both 2-chlorophenol and 4-chlorophenol inhibited alkaline phosphatase activity in a concentration dependent manner and the 50 % inhibitory concentration (IC50) was estimated to be 23.29 mM for 2-chlorophenol and 30.02 mM for 4-chlorophenol, respectively. The apparent Michaelis-Menten constant (Km) and apparent maximum reaction rate (Vmax) for the hydrolysis of 4-nitrophenyl phosphate disodium salt hexahydrate by alkaline phosphatase was found to be 0.124 mM and 1.80 μM min-1, respectively. Both Km and Vmax decreased distinctly in the presence of 2-chlorophenol and 4-chlorophenol, which indicated that the nature of the inhibition was uncompetitive type. The values of the inhibition constant (Ki) were estimated to be 18.89 mM for 2-chlorophenol and 32.68 mM for 4-chlorophenol. Therefore, 2-chlorophenol showed a stronger inhibition effect on alkaline phosphatase activity and displayed a higher affinity for the enzyme-substrate complex than 4-chlorophenol.